Nigella sativa Infusion as an Antioxidant Agent Against Gentamicin-Induced Kidney Damaged in Mice - binti Halim, Hamsiah; Achadiyani, Achadiyani; Tjahjodjati, Tjahjodjati (Althea Medical Journal, 2014)
Background: Gentamicin is one of the most common antibiotics related to nephrotoxicity. It has been proposed that the nephrotoxicity is associated with the generation of the reactive oxygen species. Thymoquinone, an active compound of Nigella sativa, shows to have an antioxidant property. The study aims to identify the possible nephroprotective action of Nigella sativa infusion against gentamicin-induced kidney damaged in mice.Methods:This experimental study was carried out in the Department of Cell Biology Laboratory, Universitas Padjadjaran, Bandung from 10th November 2012 to 14th December 2012. There were four groups, each consisting ofÂ 6 mice. Group I (control negative), group II (gentamicin 100 mg/kg), group III (3.9 mg Nigella sativa infusion+gentamicin 100mg/kg) and group IV (7.8 mg Nigella sativa infusion+gentamicin 100mg/kg). The kidneys were evaluated histopathologically by light microscope. The percentage average number of normal proximal tubules in group I and the percentage average number of proximal tubules damaged in group II, III and IV were measured.Results: The results showed the percentage average number of the proximal tubules damaged in group II, III and IV were 14.53%, 7.49% and 3.94% respectively. Significant differences were observed between group II and III, group II and IV, and group III and IV.Conclusion:Nigella sativa infusion protects against gentamicin-induced kidney damage in mice.Keywords: gentamicin, kidney, Nigella sativa infusionÂ Â Infusa Nigella sativa sebagai Antioksidan Terhadap Kerusakan Ginjal padaTikus yang Diinduksi Gentamisin Â Â LatarBelakang: Gentamisin adalah salah satu antibiotik yang paling sering dihubungkan dengan nefrotoksisitas. Nefrotoksisitas yang terjadi berhubungan dengan pembentukan reactive oxygen species. Thymoquinone, senyawa aktif Nigella sativa, telah terbukti memiliki sifat antioksidan. Penelitian ini bertujuan untuk mengidentifikasi sifat nefroprotektif infusa Nigella sativa terhadap kerusakan ginjal pada tikus yang diinduksi gentamisin.Metode: Penelitian eksperimental ini dilakukan di Laboratorium Departemen Biologi Sel, Fakultas Kedokteran, Universitas Padjadjaran, Bandung dari 10 November 2012 â14 Desember 2012. Ada empat kelompok masing-masing terdiri atas 6 tikus. Kelompok I (control negatif), kelompok II (gentamisin 100 mg /kg), kelompok III (3,9 mg Nigella sativainfus + gentamisin 100mg/kg) dan kelompok IV (7,8 mg Nigella sativa infus + gentamisin 100mg/kg). Ginjal kemudian dievaluasi secara histopatologi dengan mikroskop cahaya. Persentase rata-rata jumlah tubulus proksimal yang normal dalam kelompok I dan persentase rata-rata jumlah tubulus proksimal rusak dalam kelompok II, III dan IV diukur.Hasil: Persentase rata-rata jumlah tubulus proksimal rusak dalam kelompok II, III dan IV adalah 14,53%, 7,49% dan 3,94%. Perbedaan signifikan yang diamati adalah pada kelompok II dengan III, kelompok II denganÂ IV, serta kelompok III dan IV.Simpulan: Infusa Nigella sativa infuse melindungi terhadap kerusakan ginjal yang diinduksi gentamisin pada tikus.Kata kunci: gentamisin, ginjal, infusa Nigella sativaDOI: 10.15850/amj.v1n2.354